An approach to building Field Epidemiology Training Programme (FETP) trainees' capacities as educators - Matthew M. Griffith; Ariuntuya Ochirpurev; Takuya Yamagishi; Shingo Nishiki; Baigalmaa Jantsansengee; Tamano Matsui; Kazunori Oishi (World Health Organization Regional Office for the Western Pacific, 2018)
Field Epidemiology Training Programmes (FETPs), which are modelled after the Centers for Disease Control and Prevention's Epidemic Intelligence Service programme, began in 1980 and have produced graduates in more than 70 countries, including 12 in the Western Pacific Region.1,2 These programmes aim to "build sustainable capacity for detecting and responding to public health threats" and "develop expertise so that disease outbreaks can be detected locally and prevented from spreading".3 FETPs thus include training in applied epidemiology and public health services. FETP trainees and graduates, however, often have additional responsibilities: mentoring newer trainees, supervising in the field, leading short training courses, facilitating meetings, etc. Programmes therefore must provide trainees with the knowledge and skills to fulfil these responsibilities.